The status of arabic literature in Nigerian authorship: a chronological study (2018)
Arabic literature had been a vehement genre of Arabic literary heritage since pre and post Islamic age, being a rare source contained a compendium and anthology of Arabs, likewise, in getting more acquainted with a real classical Arabic language and civilization, had hitherto contributed to its widespread to other Islamic countries where Islam and Arabic studies have been applausive and acknowledged. It is of no doubt that the genesis of Arabic Literature in Nigeria is traced to the time Arabic studies began in the 9th Century C.E, because it led to the time Islam got to Nigeria, Albelt, going along with Islamic and Arabic Education. Since then, Arabic Nigerian Authorships have worked tremendously to promote the Status of Arabic Literature in everyday through their intellectual prowess by producing many works of note in the field of Arabic Literature. Therefore, this paper aims to examine the Status of Arabic literature of Nigerian authorship in the twenty-first Century and bring into limelight their immense contribution to the sustainability of Arabic literature in Nigeria. Before delving in to the main work , the paper would give a cursory look into general over-view on the concept of Arabic literature in human literary heritage, Likewise, the genesis of Arabic literature in Nigeria, dichotomy in the periods of Arabic literature in Nigeria, Status of Arabic literature of Nigerian authorship in the past and compare it with the present and proffer a suitable prospects in the future would be discussed.